"Keeping the Road Clear between Us": Indigenous Infrastructure and the Potential for Transformative Design - Toso, Tricia (Stream: Interdisciplinary Journal of Communication, 2018)
As scientists and science educators challenge the epistemological hegemony and cultural imperial-ism of Western modern science by insisting that definitions of science be expanded to include other scientific traditions including traditional ecological knowledge (Berkes 1988, 1993; Inglis, 1999; Warren 1997; Williams & Baines 1993; Snively & Corsigila 2000), we have not seen much of a coe-taneous movement in civil and natural resource engineering. The decolonization of Canadian cities must begin with the acknowledgement of the role engineering, architecture and urban planning has had in the perpetuation of colonialism. This paper works to identify directions for the decoloniza-tion of infrastructural systems through a reconsideration of pre-contact Indigenous architectural and infrastructural histories, a recognition of the ways in which infrastructure was often used as an instrument of colonial land claims, and the various ways in which Indigenous peoples, communities, and knowledges have contributed to the infrastructures that populate our contemporary geography. It is through an acknowledgment of infrastructure as actant in colonialism and the contributions Indigenous peoples and knowledges have had in the development and implementation of our infrastructural systems that we can begin to expand and deepen our understanding of the relationings between knowledge, infrastructure, ecosystems and Indigenous peoples. Finally, this paper considers the ways in which Indigenous design principles offer a great deal of potential in the creation of more environmentally and socially sustainable communities, and even regenerative design.